1997
DOI: 10.1038/bjc.1997.63
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of urokinase plasminogen activator and its receptor in pancreatic carcinoma

Abstract: Summary Urokinase plasminogen activator (uPA) is a serine proteinase that has been suggested to play an important role in cancer invasion and metastasis. It binds to a specific membrane receptor denominated uPA receptor (uPAR Pancreatic cancer has one of the poorest prognoses of all gastrointestinal malignancies, being the fourth or fifth leading cause of cancer-related deaths in Western industrialized countries (Bomman et al, 1994). Gudjonsson (1987), in his classical review of 37 000 patients with pancreatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
126
2
4

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(141 citation statements)
references
References 24 publications
9
126
2
4
Order By: Relevance
“…There is increasing evidence suggesting that the higher the protease level at diagnosis the worse the prognosis, 27,38 and we have shown here that there would be a critical threshold of the enzyme levels required for virus activation. Thus, not only the species but also the amounts of the proteases involved in the actual tumor will have to be included in 'individualization'.…”
Section: Mmp-dependent Cellmentioning
confidence: 67%
“…There is increasing evidence suggesting that the higher the protease level at diagnosis the worse the prognosis, 27,38 and we have shown here that there would be a critical threshold of the enzyme levels required for virus activation. Thus, not only the species but also the amounts of the proteases involved in the actual tumor will have to be included in 'individualization'.…”
Section: Mmp-dependent Cellmentioning
confidence: 67%
“…High uPA and PAI-1 levels are correlated with a poor prognosis for patients with primary breast cancer (Duffy et al, 1990;Janicke et al, 1990Janicke et al, , 1993Foekens et al, 1992Foekens et al, , 1994Grondahl-Hansen, 1993). The PA system appears to be a strong prognostic marker in breast cancer as well as in other types of cancer (Nekarda et al, 1994;Pedersen et al, 1994;Cantero et al, 1997). Recently, the prognostic significance of the uPAR in breast cancer (Grondahl-Hansen, 1995), colorectal cancer (Ganesh et al, 1994), gastric cancer (Heiss et al, 1995b), pancreatic cancer (Cantero et al, 1997) and lung cancer (Pedersen et al, 1994) has been shown.…”
Section: Discussionmentioning
confidence: 99%
“…The PA system appears to be a strong prognostic marker in breast cancer as well as in other types of cancer (Nekarda et al, 1994;Pedersen et al, 1994;Cantero et al, 1997). Recently, the prognostic significance of the uPAR in breast cancer (Grondahl-Hansen, 1995), colorectal cancer (Ganesh et al, 1994), gastric cancer (Heiss et al, 1995b), pancreatic cancer (Cantero et al, 1997) and lung cancer (Pedersen et al, 1994) has been shown. While numerous studies have reported an increase in uPA expression during transmigration of basal membranes in extracellular matrix in metastatic and non-metastatic tumour cell lines, this has not previously been investigated in breast cancer cells that have already been shedded (Ossowski et al, 1991;Henderson et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Specific inhibition of the u-PA receptor has been successful in reducing the establishment of primary tumors and metastasis after intravenous injection of tumor cells into immunodeficient mice (Ignar et al, 1998). In colorectal cancer, numerous studies have shown overexpression of u-PAR cell in contrast to the corresponding normal tissue and/or surrounding stromal cells (Cantero et al, 1997;Morita et al, 1998), and suggested u-PAR as a characteristic of the invasive or even the malignant phenotype (Sliutz et al, 1996). Colorectal cancer with a high uPAR expression has been correlated with a low 5-year survival (Ganesh et al, 1994).…”
Section: Proteolytic Enzymesmentioning
confidence: 99%